ChemInform Abstract: Synthesis and Structure—Activity Relationship Study of Cytotoxic Lupane‐Type 3β‐O‐Monodesmosidic Saponins with an Extended C‐28 Side Chain. Issue 36 (9th September 2014) - Cmoch, Piotr; Korda, Anna; Rarova, Lucie; Oklestkova, Jana; Strnad, Miroslav; Luboradzki, Roman; Pakulski, Zbigniew
Abstract Several of the compounds exhibit cyctoxicity against human cancer cell lines.